Metabolic markers in Jamaican male sprinters - Beckford, T. S.; Irving, R. R.; Golden, K. D.; Poudevigne, M. S. (New Studies in Athletics, 2017)
Studies have revealed that metabolic adaptations represent a significant contributor to successful sprinting performance. This study investigated biochemical markers of muscle metabolism in Jamaican males following a medium sprint expecting a distinction among elite, sub-elite (based on previous achievements) and control groups. Blood lactate was measured before (zero) and after (three, eight and 15 minutes) a 350m sprint. Serum creatine kinase and lactate dehydrogenase determination was done before (zero) and after (30 minutes) the sprint. One way analysis of variance revealed statistically significant differences among the groups for pre-exercise p = .015, and post-exercise n = .001 lactate dehydrogenase levels; postexercise p = .025 creatine kinase levels;and 350m sprint velocity p < .001. Positively correlated for the two groups of athletes were velocity and peak blood lactate p < ¦001. Peak blood lactate, serum creatine kinase and lactate dehydrogenase provided distinctions in performance. The authors conclude with a set of practical implications for their findings including that serum levels of key muscle enzymes provide a basis for the classification of fitness levels and the muscle's response to exercise.